Epidemiological profile of dengue cases in the state of Pernambuco, Brazil (Research, Society and Development, 2022)
Objective: to evaluate the epidemiological profile of dengue in the state of Pernambuco from 2015 to 2020. Methodology: This is a retrospective, descriptive study with a qualitative approach on the epidemiological profile of dengue cases in the state of Pernambuco from 2015 to 2020. Data collection was carried out in the Notification System for Notifiable Diseases (SINAN), linked to the Department of Informatics of the Unified Health System (DATASUS), with data collection being carried out in January 2022. Results: In the period studied, 252,695 cases of dengue were reported, most of which were female (59%), aged 20-39 (36.08%), of mixed race (40.5%), with a high prevalence of less educated. Most cases were of classic dengue diagnosed by clinical-epidemiological methods evolving to cure, and the most prevalent serotype is still unknown, with a greater number in the warmer months. Conclusion: It was evident that dengue is still very prevalent in the state of Pernambuco, underreporting and possible errors at the time of notification is a great challenge presented, which can make it difficult to combat the disease.